Did the Covid19 Increased the Risk Aversion of Investors? : Evidence from Czech Exchange Rate - Časta, Martin; Maršál, Aleš; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
The main goal of this study is to obtain expectations regarding the future development of the exchange rate using derived option probabilities and based on them to calculate the perception of risk by investors. More specifically, this study deals with the application of the Ross recovery theorem in the FOREX market using the CZK/EUR exchange rate. From a theoretical point of view, I offer an expression of the Ross recovery theorem using different Numeraire and I also propose a novel approach to the calculation of the implied risk premium. The results show that both subjective and risk-neutral densities are not unbiased estimators of a future exchange rate. However, the results show a significant increase in the implied risk aversion during the pandemic, which is primarily driven by foreign influences from the perspective of the Czech Republic.
Vedoucí práce: Aleš Maršál
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses